Nilai-Nilai Religi Dalam Efektivitas Realisasi Pendapatan Daerah Guna Mendukung Program Pembangunan Daerah - Situmorang, Efita Natasya; Manurung, Joy Fenika; Siregar, Masjamilan; Nasirwan (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the effectiveness of local revenue realization, particularly Regional Original Revenue (PAD), in supporting regional development programs. PAD serves as a vital indicator of fiscal independence and a primary funding source for sustainable development efforts. However, many regions still face significant challenges in optimizing PAD potential. Gaps between revenue targets and actual realization, weak retribution management, low taxpayer compliance, and poor inter-agency data integration are major obstacles to effectiveness. This study utilizes a descriptive method rooted in qualitative analysis by examining existing literature and secondary data analysis from credible sources. The findings indicate that PAD effectiveness strongly influences a region's fiscal capacity to implement development functions, especially in public service and infrastructure sectors. Therefore, policy reform, strengthening of revenue collection systems, and improvement of human resource capacity are critical strategies to achieve fiscal autonomy and sustainable regional development. The integration of religious values into strategies for optimizing local revenue (PAD) can also enhance tax awareness through spiritual and social approaches, strengthen public trust in the government, and foster development that is not only materially oriented but also grounded in ethics and social justice.